2018
DOI: 10.1590/s0100-204x2018001200005
|View full text |Cite
|
Sign up to set email alerts
|

Foliar and topdressing application of nitrogen to the common bean crop

Abstract: The objective of this work was to evaluate the effect of applying N sources to leaves and N rates to the soil on the growth, N uptake, and grain and crude protein yields of the common bean (Phaseolus vulgaris) crop. Three experiments -two irrigated and one rainfed -were conducted during the 2012/2013 agricultural season, in a randomized complete block design with four replicates. The treatments consisted of the application of: four N rates (0, 45, 90, and 180 kg ha -1 ) to the soil, as topdressing in the V 4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…agropec. bras., Brasília, v.53, n.11, p.1230-1238, Nov. 2018 DOI: 10.1590/S0100-204X2018001100005 macropore ratio, drainage deficiency mainly due to the low hydraulic conductivity of the B horizon or to the underlying material, and compacted subsurface layer (Gomes et al, 2006); in and below this layer, it is difficult for roots to extract water and nutrients from the soil (Calonego et al, 2011), which can affect soybean grain yield. To minimize compaction, scarification systems are commonly used in order to reduce soil density, microporosity, and the micropore/macropore ratio, as well as to increase macroporosity and total porosity (Sartori et al, 2015;Giacomeli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…agropec. bras., Brasília, v.53, n.11, p.1230-1238, Nov. 2018 DOI: 10.1590/S0100-204X2018001100005 macropore ratio, drainage deficiency mainly due to the low hydraulic conductivity of the B horizon or to the underlying material, and compacted subsurface layer (Gomes et al, 2006); in and below this layer, it is difficult for roots to extract water and nutrients from the soil (Calonego et al, 2011), which can affect soybean grain yield. To minimize compaction, scarification systems are commonly used in order to reduce soil density, microporosity, and the micropore/macropore ratio, as well as to increase macroporosity and total porosity (Sartori et al, 2015;Giacomeli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, for yield during the 2018-2019 soybean season, the treatments based on urea-formaldehyde/triazone Hexion 2 and Hexion 3 demonstrated statistically superior performance compared to treatments Hexion 1, urea solution, and the control (Table 2), providing interesting results from an agronomic point of view. Kotz-Gurgacz and coworkers, working with foliar application of urea formaldehyde in the state of São Paulo, also observed a significant increase in yield of 15.6% in the bean crop in comparison to the control [40]. When analyzing Pearson's linear correlation for the 2018-2019 soybean crop, it is observed that production showed a positive correlation of 0.36, 0.35, and 0.36 for POD 1, POD 2, and NPP, respectively (Figure 2).…”
Section: Resultsmentioning
confidence: 90%
“…Kotz-Gurgacz and coworkers, working with foliar application of urea formaldehyde in the state of São Paulo, also observed a significant increase in yield of 15.6% in the bean crop in comparison to the control [40]. When analyzing Pearson's linear correlation for the 2018-2019 soybean crop, it is observed that production showed a positive correlation of 0.36, 0.35, and 0.36 for POD 1, POD 2, and NPP, respectively (Figure 2).…”
Section: Resultsmentioning
confidence: 90%
“…These authors, evaluating different cultivars of irrigated bean in the winter under notillage systems, had a grain yield of 2,304 kg ha -1 with the 'IPR Andorinha' cultivar, under a nitrogen rate of 120 kg ha -1 . Nevertheless, Kotz-Gurgacz et al (2018), testing the 'Pérola' bean cultivar under notillage system and nitrogen rates, in two crop periods, reached grain yields of 3,342 and 2,699 kg ha -1 , respectively in the warmer (August to November) and colder (February to May) periods, in the irrigated treatments.…”
Section: Resultsmentioning
confidence: 92%